Differential growth on sutures of tendon cells derived from torn human rotator cuff. - Hakimi, O; Chaudhury, S; Murphy, R; Carr, A (2012)
Rotator cuff tendon pathology is proposed to account for 30-70% of all shoulder pain and surgical repair with a nonabsorbable suture is the common option for painful rotator cuff tears that have failed conservative treatment. A number of studies have suggested the beneficial effect of augmenting the repair with implants constructed from polymers used for sutures. Thus, it was of interest to investigate the affinity of tendon-derived fibroblasts, often thought to be the repairing agents of torn tendons, to commonly used sutures. The aim of this comparative study was to evaluate the suitability of these sutures for the construction of a patch by measuring cell survival, proliferation, and migration of human tendon-derived fibroblasts on different sutures. To ensure relevance to the target tissue, cells used in this study were obtained from torn human supraspinatus tendons. An initial comparison of cell proliferation on suture mats showed an overall positive proliferation on polyester (Ethibond) and polydioxanone (PDSII) mats and a reduction of proliferation on vicryl (polyglactin 910) compared to day one. The results also showed that the degradation products of vicryl had a negative effect on cell growth over 10 weeks. Of the commercial sutures selected and tested, Ethibond showed the best performance in terms of cell attachment and increase in biomass. The degradable PDSII also showed good interaction with cells in vitro, but relatively poor cell adhesion. This study provides useful and clinically relevant information, which could help to guide future considerations for candidate materials from which to construct tissue repair patches.